2016
DOI: 10.31235/osf.io/3twbm
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Occupy Online: Facebook and the Spread of Occupy Wall Street

Abstract: Since Occupy Wall Street began in New York City on September 17th, the movement has spread offline to hundreds of locations around the globe. Social networking sites have been critical for linking potential supporters and distributing information. In addition to Facebook pages on the Wall Street Occupation, more than 400 unique pages have been established in order to spread the movement across the US, including at least one page in each of the 50 states. These Facebook pages facilitate the creation of local en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Latency refers to the length of time it takes to share content (McFarland & Ployhart, 2015), and low latency allows users to share and access a higher level of information quickly as well as communicate rapidly. For example, social networks allow things to go viral and spread to a high number of users in almost real-time (Caren & Gaby, 2011; Mills, 2012). This characteristic, in turn, leads users to extend a high level of energy and cognitive resources to manage this communication and associated information, resulting in ego depletion.…”
Section: The Downsides Of Using Linkedin: a Self-regulatory Perspectivementioning
confidence: 99%
“…Latency refers to the length of time it takes to share content (McFarland & Ployhart, 2015), and low latency allows users to share and access a higher level of information quickly as well as communicate rapidly. For example, social networks allow things to go viral and spread to a high number of users in almost real-time (Caren & Gaby, 2011; Mills, 2012). This characteristic, in turn, leads users to extend a high level of energy and cognitive resources to manage this communication and associated information, resulting in ego depletion.…”
Section: The Downsides Of Using Linkedin: a Self-regulatory Perspectivementioning
confidence: 99%
“…For instance, as early as 1997, scholars examined the use of the internet by the Zapatista movement in Mexico and argued that the movement was able to overcome the traditional geographic constraints of access to media thanks to the “constant and reciprocal connections between cyberspace and other social spaces” [ 4 ]. Similarly, others have noted the emergence of new forms of political dissent mediated by technologies like SMS in the“Pasalo” movement in Spain [ 5 ], and by modern tools such as Facebook and Twitter during the Occupy Wall Street movement in the United States [ 6 , 7 ] and the Arab Spring in Egypt [ 8 – 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…A survey of participants in a May 2011 Occupy rally found 24% current students and 39% more already holding degrees (Milkman, Luce, & Lewis, ). Student involvement in Occupy could also be seen through the coverage within college media outlets (Reimold, ), college town social media activity (Caren & Gaby, ), and within one of the central grievances of the activists, the call for relief from the tremendous amount of student debt held nationally (Declaration of the Occupation, ). Among Occupy participants, one survey found that greater than 50% of respondents under age 30 had over $1,000 in student debt at the time (Milkman et al., ).…”
Section: Case Studiesmentioning
confidence: 99%
“…The Tumblr page, which featured user‐submitted images of individuals holding signs that told personal stories of economic strife, was a driving force behind the Occupy narrative that the average person was facing unprecedented difficulty due to the few powerful individuals at the top of the societal hierarchy. Almost immediately after it was started, the Tumblr account gathered followers in large numbers (Caren & Gaby, ). Although there were a few early participants who set general terms of the Occupy movement, members were able to bring personal narratives into the cause in a way that the movement adapted and grew iteratively to suit the needs and demands of the activists.…”
Section: Case Studiesmentioning
confidence: 99%